Development of Efficient Protocols for Stable and Transient Gene Transformation for Wolffia Globosa Using Agrobacterium - Heenatigala, P. P. M.; Yang, Jingjing; Bishopp, Anthony; Sun, Zuoliang; Li, Gaojie; Kumar, Sunjeet; Hu, Shiqi; Wu, Zhigang; Lin, Wei; Yao, Lunguang; Duan, Pengfei; Hou, Hongwei (Frontiers in Chemistry, 2018)
Members of the Wolffia genus are fascinating plants for many biologists as they are the smallest flowering plants on Earth and exhibit a reduced body plan that is of great interest to developmental biologists. There has also been recent interest in the use of these species for bioenergy or biorefining. Molecular and developmental studies have been limited in Wolffia species due to the high genome complexity and uncertainties regarding the stable genetic transformation. In this manuscript we present new protocols for both stable and transient genetic transformation for Wolffia globosa using Agrobacterium tumefaciens. For the transient transformation, we used Wolffia fronds whereas we used clusters for the stable transformation. As proof of concept we transformed two synthetic promoter constructs driving expression of the GUS marker gene, that have previously been used to monitor auxin and cytokinin output in a variety of species. Using these approaches we obtained a Transformation Efficiency (TE) of 0.14% for the stable transformation and 21.8% for the transient transformation. The efficiency of these two methods of transformation are sufficient to allow future studies to investigate gene function. This is the first report for successful stable transformation of W. globosa.